(untitled) (Sains Humanika, 2013)
The main focus of this study is to identify, the contribution of aspects of homework on the effects of homework on students. The framework of the study is based on the Theory of Task Structure by Ames (1992), the Process Model of Factors Influencing the Effectiveness of Homework by Cooper (2007), homework management framework by Zaharah (2001) and Epstein’s six-type parent involvement practices (1995). Data was collected using the survey methods, interviews and document analysis. A total of 523 Bahasa Melayu, English Language, Mathematics and Science teachers and 480 form four students from 50 secondary schools were selected as respondents, while six teachers were involved as a participant in a structured interview. Data gathered from the survey was analyzed using descriptive and inferential statistics through SPSS version 15. Regression analysis found that giving feedback, goal setting of homework and homework loads contribute significantly to the positive effects of homework.